2000
DOI: 10.1002/(sici)1097-4547(20000115)59:2<209::aid-jnr7>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of genes involved in cellular stress and apoptosis in a rat model of hippocampal degeneration

Abstract: Changes in gene expression within the hippocampus induced by denervation after electrolytic fimbria-fornix lesion in rat were compared to morphological and biochemical alterations. Fimbria-fornix lesion results in degeneration of hippocampal cholinergic terminals as evidenced by a sustained (2 days to 1 month) decrease in cholineacetyltransferase (ChAT) activity (50%). These changes were accompanied by a decrease in growth associated protein 43 (GAP-43) immunoreactivity in all hippocampal layers 4 days after l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 37 publications
(34 reference statements)
0
7
0
1
Order By: Relevance
“…This is a transcription factor that is overexpressed in hippocampal neurons just before the initiation of the apoptotic cascade that occurs when they are deprived of the cholinergic afferents (Anguelova et al ., 2000). In SCG, downregulation of this gene is consistent with the absence of deafferentation/axotomy‐induced neuronal death (Snider et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This is a transcription factor that is overexpressed in hippocampal neurons just before the initiation of the apoptotic cascade that occurs when they are deprived of the cholinergic afferents (Anguelova et al ., 2000). In SCG, downregulation of this gene is consistent with the absence of deafferentation/axotomy‐induced neuronal death (Snider et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from renal jip1 mRNA, the JIP1-3 proteins are highly expressed in the brain (Kim et al, 1999) with cytoplasmic and axonal-presynaptic distribution (Pellet et al, 2000), and complexes with MLK2 and activated JNK have been found along microtubules in ®broblasts . Expression of JIPs can be enhanced at a transcriptional level following ischemia (Hayashi et al, 2000), neuronal denervation (Anguelova et al, 2000) or inhibition of JNK (Levresse et al, 2000) with an immediate impact on JNK activation, since the overexpression of JIPs relative to JNKs blocks JNK functions (Ferrell, 2000). The JNK-associated protein 1 (JSAP1), which is synonymous to JIP-3 and displays a preference for JNK3 (Ito et al, 1999), antagonizes the activation of ERKs by inhibition of the Raf-1 mediated MEK1 phosphorylation (Kuboki et al, 2000).…”
Section: Regulation Of Pathological-degenerative Functions Of the C-jmentioning
confidence: 99%
“…At the physiological level, cholinergic neurotransmission is altered under stress (Kaufer et al 1998; Soreq and Seidman 2001). These stress-induced changes are mostly attributed to the combinatorial regulation of many genes’ altered transcription levels (Anguelova et al 2000). However, the contribution of posttranscriptional regulation mechanisms to these stress-associated responses is increasingly acknowledged (Battaglia and Ogliari 2005; Gattoni et al 1996; Meshorer et al 2005).…”
Section: Introductionmentioning
confidence: 99%